Pengangkatan ‘Anak Adat’ Pada Suku Malind di Kabupaten Merauke - Jaya Setiawan Sinaga; Raymond P. Fenetiruma; Handika D. A Pelu (Jurnal Restorative Justice, 2021)
Adoption is a common legal event in Indonesia, including in the Malind tribe in Merauke Regency. However, there is something unique in the costumary of Malind tribe where there is a ritual of adopting an adult, even married person who come from outside the Malind tribe, known as anak adat. This study aims to determine the ritual procession of adoption of ‘anak adat’ according to the customary law of the Malind Tribe and to determine the implications that occur in connection with the adoption. The results of this research show that (1) The adoption of customary children in the Malind Tribe is carried out with a traditional ritual that lasts all night and ends with the inauguration of the customary chief who is given the name and clan of Malind and a plot of land from the clan land to own. (2) The implication of the ritual of adopting customary children creates rights and obligations for indigenous children in their status as members of the Malind indigenous community and results in a break in the kinship between the customary child and the previous tribe. Keywords: Adoption; Customary law; Malind Tribe.